Safety and Immunogenicity of ND Vaccines Used in Nepal - Marahatta, S; Upadhyaya, N; Shah, S; Sedhai, S; Sharma, P; Dhakal, S (Nepalese Veterinary Journal, 2023)
Viral infections, including Newcastle disease (ND), constitute a major health problem in the rapidly growing poultry industry of Nepal. Despite regular vaccination in the commercial farms, ND virus (NDV) outbreaks are frequently reported raising concern over the safety and immunogenicity of live-attenuated vaccines being used. This study was performed to compare the safety and immunogenicity of four commercially available ND vaccines in Nepal after administration at recommended (1X) and higher (10X) dose. There was no safety concern associated with the use of lentogenic live-attenuated ND vaccines even at higher dose. A varying degree of antibody response was observed at recommended and higher doses with the thermostable I-2 vaccine outperforming other groups. A higher dose did not improve antibody response except for the F1 vaccine. To prevent widespread outbreaks in future, regular molecular surveillance to identify the circulating strains of NDV together with the periodic evaluation of immunogenicity and protective efficacy of commercial vaccines is necessary in Nepal.